Ionic Liquids and Deep Eutectic Solvents based Ionic Nanoreactors for Advanced Applications in Colloidal Chemistry and Biomass Processing - Kumar, Arvind (RSYN Proceedings, 2025)
Ionic liquids (ILs) are the organic analogues of inorganic molten salts with melting temperature < 100oC, whereas deep eutectic solvents (DESs) are formed from a eutectic mixture of Lewis or Brønsted acids and bases which can contain a variety of anionic and/or cationic species and now widely acknowledged as a new class of ionic liquid (IL) analogues because they share many characteristics with ILs in terms of solvent properties such as low volatility, high thermal stability, wide liquid range and good solvating ability. Superior physicochemical properties distinguish ILs and DESs from conventional organic solvents, and fast replacing these in several chemical applications.The presentation is mainly focused on synthesis and application of ILs/DESs in authors laboratory and is divided in two parts. First part will cover formulation of colloidal systems using surfactant like ILs and ILs/DESs as dispersion medium. Applications of such systems in materials synthesis and preservation of biomaterials at elevated temperatures will be discussed. We have shown that IL based colloidal structures are highly thermally stable. These formulations have been used as as nanoreactors for preservation of biomaterials at elevated temperatures and as templates for preparation of shape/size-controllednanomaterials/quantum dots, metal organic frame works (MOFs) with enhanced quantum efficiency for light harvesting and also for gas adsorption/storage for energy applications.Second part of presentation deals with the use of ILs in biomass processing for clean separation of biopolymers (cellulose, hemicellulose and lignin) and recovery of other value-added chemicals. We have developed strategies to depolymerize the biopolymers at ambient conditions, for example lignin has been valorized efficiently using metal based ionic liquid systems in order to convert value added chemicals. Biopolymers dissolved in ILs/DESs have been utilized to prepare ionogles for diverse applications.
Keywords: Ionic liquids; Electrolyte; Biopolymer